2015
DOI: 10.1051/0004-6361/201526483
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Fraunhofer lines in solar brightness variability

Abstract: Context. The solar brightness varies on timescales from minutes to decades. A clear identification of the physical processes behind such variations is needed for developing and improving physics-based models of solar brightness variability and reconstructing solar brightness in the past. This is, in turn, important for better understanding the solar-terrestrial and solar-stellar connections. Aims. We estimate the relative contributions of the continuum, molecular, and atomic lines to the solar brightness varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 100 publications
1
43
0
Order By: Relevance
“…One can expect that the facular contrast in Sun-like stars depends on the stellar brightness temperature (cf. Beeck et al 2015) and on the stellar metallicity (since the facular contrast is strongly affected by the weak atomic and molecular lines, see Shapiro et al 2015). A small change of the facular contrast might break a delicate balance between facular and spot contributions to Strömgren b and y photometry and significantly increase the stellar brightness variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One can expect that the facular contrast in Sun-like stars depends on the stellar brightness temperature (cf. Beeck et al 2015) and on the stellar metallicity (since the facular contrast is strongly affected by the weak atomic and molecular lines, see Shapiro et al 2015). A small change of the facular contrast might break a delicate balance between facular and spot contributions to Strömgren b and y photometry and significantly increase the stellar brightness variability.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 demonstrates that the spectral dependences of the spot and facular components are remarkably different. The facular component has a very complex profile due to the strong influence of Fraunhofer lines (Unruh et al 1999(Unruh et al , 2008Shapiro et al 2015). The effect of Fraunhofer lines on the spot component is much more subtle and exposes itself as barely visible spikes superposed on otherwise undulating dependence (see discussion in Unruh et al 2008;Shapiro et al 2015).…”
Section: Activity Cycle Timescalementioning
confidence: 99%
See 1 more Smart Citation
“…9). (Shapiro et al 2015). Together with the inclination of the rotation axis, metallicity is also known to have an effect on the visibility of activity-related phenomena like spots and faculae (Shapiro et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that SATIRE-S reproduces the correct level of the variation in the Mn line provides strong support to the overall spectral profile of the irradiance variability computed with SATIRE-S. On the one hand, Yeo et al (2015) have recently demonstrated that the magnitude of the changes in the UV returned by SATIRE-S agrees well with the most stable satellite measurements. On the other hand, since spectral lines determine the amplitude and even the A33, page 7 of 8 phase of the visible irradiance variations (Shapiro et al 2015), our finding here indicates that the magnitude of the variability in the visible is also adequate. Finally, the model also reproduces the changes in the TSI that are dominated by changes in the UV and the visible and are measured far more reliably than changes in the spectral irradiance (Yeo et al 2014a).…”
Section: Discussionmentioning
confidence: 52%